Iron-Sensitive Cardiac Magnetic Resonance Imaging for Prediction of Ventricular Arrhythmia Risk in Patients With Chronic Myocardial Infarction. (August 2015) - Cokic, Ivan; Kali, Avinash; Yang, Hsin-Jung; Yee, Raymond; Tang, Richard; Tighiouart, Mourad; Wang, Xunzhang; Jackman, Warren S.; Chugh, Sumeet S.; White, James A.; Dharmakumar, Rohan
<x xml:space="preserve">Abstract</x> Background— Recent canines studies have shown that iron deposition within chronic myocardial infarction (CMI) influences the electric behavior of the heart. To date, the link between the iron deposition and malignant ventricular arrhythmias in humans with CMI is unknown. Methods and Results— Patients with CMI (n=94) who underwent late-gadolinium-enhanced cardiac magnetic resonance imaging before implantable cardioverter-defibrillator implantation for primary and secondary preventions were retrospectively analyzed. The predictive values of hypointense cores (HIC) in balanced steady-state free precession images and conventional cardiac magnetic resonance imaging and ECG malignant ventricular arrhythmia parameters for the prediction of primary combined outcome (appropriate implantable cardioverter-defibrillator therapy, survived cardiac arrest, or sudden cardiac death) were studied. The use of HIC within CMI on balanced steady-state free precession as a marker of iron deposition was validated in a canine MI model (n=18). Nineteen patients met the study criteria with events occurring at a median of 249 (interquartile range of 540) days after implantable cardioverter-defibrillator placement. Of the 19 patients meeting the primary end point, 18 were classified as HIC+, whereas only 1 was HIC−. Among the cohort in whom the primary end point was not met, there were 28 HIC+ and 47 HIC− patients. Receiver operating characteristic curve analysis demonstrated an additive predictive value of HIC for malignant ventricular arrhythmias with an increased area under the curve of 0.87 when added to left ventricular ejection fraction (left ventricular ejection fraction alone, 0.68). Both cardiac magnetic resonance imaging and histological validation studies performed in canines demonstrated that HIC regions in balanced steady-state free precession images within CMI likely result from iron depositions. Conclusions— Hypointense cores within CMI on balanced steady-state free precession cardiac magnetic resonance imaging can be used as a marker of iron deposition and yields incremental information toward improved prediction of malignant ventricular arrhythmias.